Adolescence continuity, change, and diversity - Cobb, Nancy J. (New York McGraw-Hill, an imprint of The McGraw-Hill Companies, Inc., 2007)
Nancy Cobb’s Adolescence, recognized as one of the leading texts in the field, provides an up-to-date and thorough review of current research and theory. Praised for its clear and engaging writing style, this highly acclaimed text is distinguished by its excellent coverage of gender, ethnicity, and identity, and for its treatment of differences between early and late adolescence. Research Focus Boxes in each chapter provide comprehensive coverage of developmental research methods. Additionally, In More Depth boxes on topics of special interest to students extend the coverage of each chapter.
Chapter 1 Defining Adolescents: Who Are They? Chapter 2 Theoretical Foundations of Adolescent Development Chapter 3 The Biological and Physical Changes of Adolescence Chapter 4 The Cognitive and Intellectual Changes of Adolescence Chapter 5 Defining the Self: Identity and Intimacy Chapter 6 The Sexual Self: Close Relationships in Adolescence Chapter 7 Adolescents in the Family: Changing Roles and Relationships Chapter 8 Adolescents and Their Friends Chapter 9 Adolescents in the Schools Chapter 10 Work, Careers, and College: New Decisions, New Ways of Thinking Chapter 11 Facing the Future: Values in Transition Chapter 12 The Problems of Youth Chapter 13 Positive Development in Adolescence: Meeting the Challenges and Making It Work Chapter 14 Studying Adolescence: Research Methods and Issues.
Previous edition: 2004.
Includes bibliographical references (pages R1-R28) and indexes.
Keywords: Adolescence; Adolescent psychology; Teenagers -- United States